Modelling the prestress transfer in pre-tensioned concrete elements - Abdelatif, Amged O.; Owen, John S.; Hussein, Mohammed F.M. (Elsevier, 2015)
Three models were developed to simulate the transfer of prestress force from steel to concrete in pre-tensioned concrete elements. The first is an analytical model based on the thick-walled cylinder theory and considers linear material properties for both steel and concrete. The second is an axi-symmetric finite element (FE) model with linear material properties; it is used to verify the analytical model. The third model is a three dimensional nonlinear FE model. This model considers the post-cracking behaviour of concrete as well as concrete shrinkage and the time of prestress releasing. A new expression from the analytical model is developed to estimate the transmission length as well as the stress distribution along the tendon. The paper also presents a parametric study to illustrate the impact of diameter of prestressing steel, concrete cover, concrete strength, initial prestress, section size, surface roughness of prestressing steel, time of prestress release, and the member length on the transfer of stress in pre-tensioned concrete elements.